Very-high-energy γ-Ray Emission from Young Massive Star Clusters in the Large Magellanic Cloud - Aharonian, F.; Benkhali, F. Ait; Aschersleben, J.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Bolmont, J.; et al. (Astrophysical Journal Letters, 2024)
The Tarantula Nebula in the Large Magellanic Cloud is known for its high star formation activity. At its center lies the young massive star cluster R136, providing a significant amount of the energy that makes the nebula shine so brightly at many wavelengths. Recently, young massive star clusters have been suggested to also efficiently produce very high-energy cosmic rays, potentially beyond PeV energies. Here, we report the detection of very-high-energy γ-ray emission from the direction of R136 with the High Energy Stereoscopic System, achieved through a multicomponent, likelihood-based modeling of the data. This supports the hypothesis that R136 is indeed a very powerful cosmic-ray accelerator. Moreover, from the same analysis, we provide an updated measurement of the γ-ray emission from 30 Dor C, the only superbubble detected at TeV energies presently. The γ-ray luminosity above 0.5 TeV of both sources is (2-3) × 1035 erg s−1. This exceeds by more than a factor of 2 the luminosity of HESS J1646−458, which is associated with the most massive young star cluster in the Milky Way, Westerlund 1. Furthermore, the γ-ray emission from each source is extended with a significance of >3σ and a Gaussian width of about 30 pc. For 30 Dor C, a connection between the γ-ray emission and the nonthermal X-ray emission appears likely. Different interpretations of the γ-ray signal from R136 are discussed.
CRIS-Team Scopus Importer:2024-08-02